0739 Comparison Of Parent And Child Treatment Preferences For Obstructive Sleep Apnea. (12th April 2019) - Combs, Daniel; Abraham, Ivo; Hsu, Chiu-Hsieh; Morgan, Wayne; Patel, Salma; Parthasarathy, Sairam
Abstract: Introduction: Obstructive sleep apnea (OSA) is common in children and is associated with negative neurocognitive and behavioral effects. While adenotonsillectomy is typically the first-line recommended therapy for OSA in children, other therapeutic options include medication therapy with montelukast (with or without intranasal steroid) and positive airway pressure therapy (PAP). To our knowledge, no prior studies have examined parent and child treatment preferences for OSA. Given this, our objective was to compare OSA treatment preferences between parents and children. Methods: Children with a new diagnosis of OSA (obstructive apnea-hypopnea index ≥1) were recruited from the pediatric sleep medicine clinic. Parent and child separately rated each available treatment option (adenotonsillectomy, medication, PAP or watchful waiting) on a scale from 0-100. A percent preference for each treatment was created by dividing the rating for each individual treatment by the sum of the ratings for all treatments. Intraclass correlation coefficients (ICC) were used to determine the level of agreement between parent and child preference for each therapy, and t-tests were used to compare the overall differences between parent and child preference for each therapy. Results: Eighteen children, mean age 11.1 ± 2.8 years, participated in the study. 61% selected adenotonsillectomy, 11% chose medication therapy, 22% chose PAP and 6% chose watchful waiting. Parent-child agreement was excellent for adenotonsillectomy (ICC=0.798, p=0.001) and PAP (ICC=0.816, p=0.001). Limited agreement was seen for watchful waiting (ICC=0.342, p=0.20) and medical therapy (ICC=0.335, p=0.21). Comparison of parent and child mean preference showed no significant difference in parent vs. child preference for adenotonsillectomy (mean preference 36% vs 35%, p=0.89), PAP (mean 29% vs 26%, p=0.43), medication therapy (mean 23% vs 26%, p=0.55) or watchful waiting (mean 12% vs 13%, p=0.81). Conclusion: Parents and children have similar preferences for OSA treatment. There was a high level of agreement for adenotonsillectomy and PAP therapy between children and parents, with lesser agreement for medical therapy and watchful waiting. Based on these results, parent treatment preference appears to be a good proxy for child preference. Support (If Any): Grant from the AASM Foundation